A relational recasting of the principles of emotional competence. Issue 6 (2nd November 2018) - Campos, Joseph J.; Camras, Linda A.; Lee, Randy T.; He, Minxuan; Campos, Rosemary G.
ABSTRACT: Carolyn Saarni's theory of emotional competence has made a central contribution by directing attention to some important functions of emotion in social interaction. Her work is permeated with examples of how emotions function within both successful and unsuccessful social interactions and relationships. An examination of her stated principles of emotional competence suggest in places a perspective that is primarily intrapsychic in nature, harking back to the early roots of emotion theory and research. In this piece, we note where Saarni has advanced implications of a relational theory of emotion for understanding emotional competence. In addition, we reframe some of Saarni's principles to make them more consistent with current relational approaches to emotion. Finally, we offer additions and extensions that we believe are compatible with the general direction of her thinking before her untimely death.